2015
DOI: 10.1097/dss.0000000000000548
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Efficacy of Full-Facial Rejuvenation Using a Combination of Botulinum Toxin Type A and Hyaluronic Acid Filler

Abstract: The combination of BoNT-A (s.U) and HA fillers results in high patient satisfaction and in an overall improvement of aesthetic outcomes and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
(31 reference statements)
0
22
0
2
Order By: Relevance
“…The approach taken in this group of patients reflects the current trend within facial aesthetic medicine, which is moving away from treatment of specific modules, toward a more holistic, full‐face approach. A number of other studies have demonstrated the efficacy and safety of this paradigm, based on evaluations of full‐face rejuvenation with injectable treatments . However, most were based primarily on fillers, and few studies have assessed the use of a full‐face approach with BoNTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach taken in this group of patients reflects the current trend within facial aesthetic medicine, which is moving away from treatment of specific modules, toward a more holistic, full‐face approach. A number of other studies have demonstrated the efficacy and safety of this paradigm, based on evaluations of full‐face rejuvenation with injectable treatments . However, most were based primarily on fillers, and few studies have assessed the use of a full‐face approach with BoNTA.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies have demonstrated the efficacy and safety of this paradigm, based on evaluations of full-face rejuvenation with injectable treatments. [16][17][18][19][20][21][22][23][24] However, most were based primarily on fillers, and few studies have assessed the use of a fullface approach with BoNTA.…”
Section: Discussionmentioning
confidence: 99%
“…32-38 This type of full face treatment also results in very high (>90%) patient satisfaction scores. 36,38 …”
Section: Aesthetic Developmentsmentioning
confidence: 99%
“…33,36,39 One explanation for this is that fillers have a greater duration of action than neurotoxin, meaning that the return to baseline is more gradual. In addition, the relaxation effect of BoNT-A may assist the dermal filler to achieve better wrinkle smoothing effects.…”
Section: Aesthetic Developmentsmentioning
confidence: 99%
“…A search of PubMed using the terms “filler + face/facial + India/Indian” and “botulinum + face/facial + India/Indian” revealed 24 articles concerned with facial rejuvenation, after omitting those that focused on hyperhidrosis, ophthalmic applications, and dentistry. 5 , 9 , 14 – 35 Despite the increasing popularity of combination treatment with botulinum toxin and hyaluronic acid (HA) fillers worldwide, 2 , 36 few articles describe their combination use in Indians in any detail. 21 , 26 , 31 In the guidelines on botulinum toxin 33 and filler 32 use published previously by other Indian authors, recommendations aimed at Caucasians were often referenced.…”
Section: Introductionmentioning
confidence: 99%